Analysis of Factors Affecting the Quality of Local Government Financial Report Information - Akhmad Saebani (Budapest International Research and Critics University, 2022)
This study examined the influence of human resource competence, utilization of information technology, and internal control of accounting on the quality of information on local government financial reports on SKPD in DKI Jakarta Province. The population in this study is the Regional Device Work Unit (SKPD) of the local Government in the area of DKI Jakarta Province. The technique of determining the sample using a simple random sampling method. The sample used in this research is a financial officer who works on SKPD DKI Jakarta Provincial Government. The number of samples used is 71 respondents. The type of data in this study is quantitative data sourced from the primary data—methods of data collection by distributing questionnaires. The scale used in the preparation of the questionnaire was the Likert scale. The data analysis method was done by validity, reliability, normality, multicollinearity, and heteroscedasticity tests. Hypothesis testing of this research using multiple linear regression analysis. The test tool for the hypothesis is a t-test and coefficient of determination (R2). The result of this research is the influence of each independent variable on the dependent variable that the competence of human resources and internal control of accounting has a significant effect on the quality of the information in local government financial reports. At the same time, the utilization of information technology has no significant effect on the quality of information on local government financial statements.